Chapter 2 The Evolution of Cities and Suburbs - Levine, Myron A. (Taylor & Francis, 2019)
Urban Politics blends the most insightful classic and current political science and related literature with current issues in urban affairs. The book's integrative theme is 'power,' demonstrating that the study of urban politics requires an analysist to look beyond the formal institutions and procedures of local government. The book also develops important subthemes: the impact of globalization; the dominance of economic development over competing local policy concerns; the continuing importance of race in the urban arena; local government activism versus the 'limits' imposed on local action by the American constitutional system and economic competition; and the impact of national and state government action on cities. Urban Politics engages students with pragmatic case studies and boxed material that use classic and current urban films and TV shows to illustrate particular aspects of urban politics. The book's substantial concluding discussion of local policies for environmental sustainability and green cities also appeals to today's students. Each chapter has been thoroughly rewritten to clearly relate the content to current events and academic literature, including the following: the importance of the intergovernmental city the role of local governments as active policy actors and vital policy makers even in areas outside traditional municipal policy concerns the prospects for urban policy and change in and beyond the Trump administration, including the ways in which urban politics is affected by, but not determined by, Washington. Mixing classic theory and research on urban politics with the most recent developments and data in urban and metropolitan affairs, Urban Politics, 10e is an ideal introductory textbook for students of metropolitan and regional politics and policy. The book's material on citizen participation, urban bureaucracy, policy analysis, and intergovernmental relations also makes the volume an appropriate choice for Urban Administration courses.